Efektivitas Pemberdayaan Penyandang Disabilitas Tuna Rungu-Wicara Melalui Program Pelatihan (Studi Pada Dinas Sosial Kota Batu) - Noberta Feri (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2022)
AbstractBasically, people with disabilities are part of the citizens who have the same rights and obligations. In Batu City alone, the number of people with disabilities is 398 people. This research discusses the role of the Social Service in empowering people with disabilities in Batu City. One of the efforts made by the Batu City Government is to provide training in the form of clothing screen printing activities carried out by the Batu City Social Service. This study aims to find out and examine how effective the training program for persons with disabilities is, using qualitative research methods and carried out with observation, interview and documentation techniques as techniques in data collection. The indicators used to measure the effectiveness of such skill programs are indicators of the achievement of goals and indicators of real chang. Based on data analysis, it can be concluded that the training program implemented by the Batu City Social Service can be said to be effective based on the benchmarks of the two indicators, where this training program has achieved the size of both indicators of achieving goals and real changes. It can be seen from the indicators of achieving the objectives that this training program is tailored to the will and abilities of people with disabilities. As well as indicators of real changes that there are psychological or mental changes of the trainees. Keywords : Effectiveness, Coach Program, Persons with Disabilities